Chronostratigraphy and paleomagnetism of the Balsas Group in the Tuzantlán-Copalillo basin, northern Guerrero state, Mexico - Roberto S. Molina-Garza; Amabel Ortega-Rivera (Revista Mexicana de Ciencias Geológicas)
The Cenozoic sedimentary fill of the Tuzantlán-Copalillo basin, in northeast Guerrero state, Mexico, is assigned to two distinct stratigraphic units. The first unit consists of a ~200 m thick fining upward section that grades eastward from massive cobble and boulder conglomerate into interbedded coarse conglomeratic sandstone and mudstone. The sandstone and mudstone facies of this unit has been referred to as the Zacango beds, but together with the conglomeratic section to the west it is here assigned to the Balsas Group based on demonstrable correlation and lateral facies changes that link these strata. The second unit disconformably overlies the Balsas Group, and comprises a tuffaceous fluvio-lacustrine unit that has been mapped as the Oapan Formation. These strata are lithologically dissimilar to the formally defined Oapan Formation elsewhere in the Balsas river basin. We do not consider the fluvio-lacustrine tuffaceous unit part of the Balsas depositional cycle; we note, however, that including these strata in the Oapan Formation thus requires a re-definition of this unit. Volcanic rhyolitic rocks were emplaced near the end of the Balsas depositional event, and locally they are interbedded in the sequence. Mineral separates of biotite and sanidine for one of these volcanic units produced concordant 40Ar/ 39Ar dates of ca. 33 Ma. We hypothesize that emplacement of volcanic rocks changed the depositional style in the basin by reducing stream gradient and closing drainages. Oapan strata were thus deposited under different conditions than the Balsas Group. Magnetostratigraphic sampling of a ~130 m thick composite section from two localities, suggests that that the Balsas Group sequence in the Tuzantlan-Copalillo basin was deposited in the interval between chrons C17n and C12r, between about 37 and 32 Ma. The mean paleomagnetic direction for the Amacuzac river locality (D=340.8º, I=34.3º; k=62.6, n=9, a95=6.6º) is slightly discordant, whilst at the Acapulco highway locality (D=351.0º, I=39.9º; k=70.4, n=9, a95=6.2º) the direction is concordant. The Amacuzac river result indicates a 13.2° ± 8° counterclockwise rotation with respect to the reference direction, and it is attributed to transpression in the region. However, the Balsas Group does not record rotations as high as those observed in Cretaceous and Paleocene rocks, which demonstrates that the process responsible for the rotations was waning by Early-Oligocene time.